2021
DOI: 10.3389/fnut.2021.729427
|View full text |Cite
|
Sign up to set email alerts
|

A Maternal High Fat Diet Leads to Sex-Specific Programming of Mechanical Properties in Supraspinatus Tendons of Adult Rat Offspring

Abstract: Background: Over half of women of reproductive age are now overweight or obese. The impact of maternal high-fat diet (HFD) is emerging as an important factor in the development and health of musculoskeletal tissues in offspring, however there is a paucity of evidence examining its effects on tendon. Alterations in the early life environment during critical periods of tendon growth therefore have the potential to influence tendon health that cross the lifespan. We hypothesised that a maternal HFD would alter bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The influence of maternal intrauterine exposure to adverse factors on the offspring health of different sexes has always been an important topic in fetal-derived diseases [ 6 , 24 , 25 , 38 , 39 ]. The single-factor analysis, multiple-factor analysis, and mediation effect analysis showed that a high-fat diet during pregnancy had a larger influence on the offspring’s HW/BW.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of maternal intrauterine exposure to adverse factors on the offspring health of different sexes has always been an important topic in fetal-derived diseases [ 6 , 24 , 25 , 38 , 39 ]. The single-factor analysis, multiple-factor analysis, and mediation effect analysis showed that a high-fat diet during pregnancy had a larger influence on the offspring’s HW/BW.…”
Section: Discussionmentioning
confidence: 99%
“…Cola1 expression was elevated in the myocardium of mice on a high-fat diet [ 50 ]. Another study indicated that Cola1 expression was abnormal in the tendon tissue of offspring on a high-fat diet [ 38 ]. In combination with the results of the present study, it was likely that a high-fat diet was involved in the regulation and expression of Cola1 , and its specific mechanism deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A directionality plugin for the Fiji-ImageJ (Ashburn, VA, USA) was used on AFM-scanned images to perform the 2D fast-Fourier transform analysis for the collagen fiber directionality measurement. 29 The directionality plugin calculates the spatial orientation of the fibers in an image and generates a normalized histogram with the amount of the fiber present between 0 and 180°. A Gaussian distribution is fitted on the generated histogram, calculating the goodness of the fit.…”
Section: Directionality Analysismentioning
confidence: 99%